Transfer RNA-Derived Fragments, the Underappreciated Regulatory Small RNAs in Microbial Pathogenesis - Li, Zhongyou; Stanton, Bruce A. (Frontiers in Microbiology, 2021)
In eukaryotic organisms, transfer RNA (tRNA)-derived fragments have diverse biological functions. Considering the conserved sequences of tRNAs, it is not surprising that endogenous tRNA fragments in bacteria also play important regulatory roles. Recent studies have shown that microbes secrete extracellular vesicles (EVs) containing tRNA fragments and that the EVs deliver tRNA fragments to eukaryotic hosts where they regulate gene expression. Here, we review the literature describing microbial tRNA fragment biogenesis and how the fragments secreted in microbial EVs suppress the host immune response, thereby facilitating chronic infection. Also, we discuss knowledge gaps and research challenges for understanding the pathogenic roles of microbial tRNA fragments in regulating the host response to infection.